Propiedad indígena y titulación de tierras en la Amazonía boliviana, 1842-1880 - Anna Guiteras Mombiola (Caravelle)
Native inhabitants in Beni acquired, through the decree of 06.08.1842, the category of citizens «capable of equality, liberty and property rights». Knowledge of these regulations allowed, between 1842 and 1880, indigenous people to develop different strategies in order to protect the lands they occupied and which they used for agriculture and forestry activities, by getting communal and private property deeds.